A comparative study on thermal behavior of solid-state light trivalent lanthanide isonicotinates in dynamic dry air and nitrogen atmospheres - Nunes, W. D. G. [UNESP]; Teixeira, J. A. [UNESP]; Nascimento, A. L. C. S. do [UNESP]; Caires, F. J. [UNESP]; Ionashiro, E. Y.; Ionashiro, M. [UNESP] (Springer, 2016)
Characterization, thermal stability, and thermal decomposition of light trivalent lanthanide isonicotinates Ln(L)(3)center dot 2H(2)O (Ln = La to Gd, except Pm; L = isonicotinate) were investigated employing simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), DSC, infrared spectroscopy (FTIR), evolved gas analysis by TG-DSC coupled to FTIR, elemental analysis, and complexometry. The dehydration of these compounds occurs in a single step, and the thermal decomposition of the anhydrous compounds occurs in one or two (air) and two or three steps (N-2). The final residues of thermal decomposition were CeO2, Pr6O11, and Ln(2)O(3) (Ln = La, Nd to Gd) in air atmosphere, while in N-2 atmosphere the mass loss is still being observed up to 1000 A degrees C. The results also provided information concerning the gaseous products evolved during the thermal decomposition in dynamic dry air and nitrogen atmospheres.
Keywords: Lanthanide isonicotinates; Thermal behavior; Evolved gas analysis